‘Uncomfortable and Embarrassed’: The Stigma of Gastrointestinal Symptoms as a Barrier to Accessing Care and Support for Collegiate Athletes - Jennifer A. Jamieson; Cayla Olynyk; Ruth Harvie; Sarah O’Brien (Dietetics, 2025)
This study aimed to explore the occurrence of exercise-associated gastrointestinal symptoms (ExGIS) in collegiate athletes and identify related self-management practices. A sequential mixed methods design was used, consisting of an online survey followed by semi-structured interviews. Data were analyzed with descriptive statistics (survey) and thematic analysis (interviews). Survey respondents (n = 96) represented various individual and team sports but were primarily female (76%). ExGIS prevented or interrupted training and/or competition in 32%. Female athletes experienced gastrointestinal symptoms (GIS) more frequently at rest (60%) and during training (37%), compared to males (22% and 9%, respectively; p < 0.01). Only 12% sought health care for ExGIS. Four (13%) female runners with ExGIS agreed to an interview. Response rates and interview data provided evidence of stigma in discussing GIS. Self-imposed food restriction was a common self-management strategy. In summary, female collegiate athletes may experience a greater burden of GIS and ExGIS than males. The stigmatized topic of ExGIS is a potential barrier to seeking health care and support. Access to a sport dietitian could help to address barriers to ExGIS care and support self-management practices in these athletes.